2003
DOI: 10.1163/156915903322555513
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo as a building material alternative for Western Europe? A study of the environmental performance, costs and bottlenecks of the use of bamboo (products) in Western Europe

Abstract: For two bamboo products, bamboo in its natural form (the culm) and in an industrial form (as a panel), the environmental impact was determined and compared to alternatives. This comparison was made using a model that uses data from Life Cycle Assessment (LCA), based on the use of these products in the Netherlands. The consequences of the application of bamboo culm in the building process of 5 bamboo building projects in Western Europe were also analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 5 publications
0
16
0
2
Order By: Relevance
“…Much previous LCA research on building has focused on assessing energy consumption and environmental emissions in the whole life cycle of two kinds of buildings: residential building (Asif et al 2007;Adalberth et al 2001;Blengini and Di Carlo 2010) and official building (Scheuer et al 2003;Junnila 2004;Li 2006a;Kofoworola and Gheewala 2008). Other research is related with building materials, such as concrete (Borjesson and Gustavsson 2000;Lenzen and Treloar 2002;Gustavsson and Sathre 2006;Peyroteo et al 2007), steel (Peyroteo et al 2007), wood (Borjesson and Gustavsson 2000;Lenzen and Treloar 2002;Petersen and Solberg 2005;Gustavsson and Sathre 2006), bamboo (Van der Lugt et al 2003), ceramic (Nicoletti et al 2002) and marble tiles (Van der Lugt et al 2003), or analyzed environmental impacts in the subsystems of building, such as electrical and thermal energy system (Osman and Ries 2007), wood floor system (Nebel et al 2006), heating, and air conditioning system (Prek 2004;Shah et al 2008). Few LCAs of buildings specialized in evaluating GHG emission or compared complete building materials.…”
Section: Introductionmentioning
confidence: 99%
“…Much previous LCA research on building has focused on assessing energy consumption and environmental emissions in the whole life cycle of two kinds of buildings: residential building (Asif et al 2007;Adalberth et al 2001;Blengini and Di Carlo 2010) and official building (Scheuer et al 2003;Junnila 2004;Li 2006a;Kofoworola and Gheewala 2008). Other research is related with building materials, such as concrete (Borjesson and Gustavsson 2000;Lenzen and Treloar 2002;Gustavsson and Sathre 2006;Peyroteo et al 2007), steel (Peyroteo et al 2007), wood (Borjesson and Gustavsson 2000;Lenzen and Treloar 2002;Petersen and Solberg 2005;Gustavsson and Sathre 2006), bamboo (Van der Lugt et al 2003), ceramic (Nicoletti et al 2002) and marble tiles (Van der Lugt et al 2003), or analyzed environmental impacts in the subsystems of building, such as electrical and thermal energy system (Osman and Ries 2007), wood floor system (Nebel et al 2006), heating, and air conditioning system (Prek 2004;Shah et al 2008). Few LCAs of buildings specialized in evaluating GHG emission or compared complete building materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to literature reviews, mass and energy balance data for bioethanol production were obtained from the AspenPlus™ model. The inventory data of bamboo plantation and harvesting (Table 3) are derived from van der Lugt et al (2003) 28 and the assumptions about transportation are listed in Table 4. The life time of bamboo is 20 years with the culms productivity of 48 dry ton/ha per year.…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…Bamboo is a kind of fast growing material with renewable, natural, and biodegradable properties (Bonilla et al, 2010), which makes it an exceptional economic resource for wide use. Moreover, studies indicated that the environmental performance of bamboo was favorable compared to timber in energy consumption and environmental costs (Van der Lugt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%